The Research Activity of Rev. Prof. Remigiusz Sobański in the Field of Substantive Canon Law = Activité scientifique du Révérend Professeur Remigiusz Sobański dans le domaine du droit canonique du mariage = L’attività di ricerca del sacerdote professor Remigiusz Sobański nel campo del diritto matrimoniale canonico - Góralski, Wojciech (Philosophy & canon law, 2022)
Remigiusz Sobański (1930-2010), a long-time professor at the Faculty of Canon Law of the Academy of Catholic Theology in Warsaw, and then at Cardinal Stefan Wyszyński University in Warsaw. Although his research focused mainly on the theory of canon law, he also published several dozen works in the field of canonical matrimonial law. These works cover four main research areas: marriage law (general rules), marriage consent, form of marriage, mixed marriages. Moreover, as a judicial vicar, he prepared and published several dozen sentences in the cases of nullitatis matrimonii.